Experimental dataset on the dispersion stability of natural polymer non-covalently functionalized graphene nanoplatelets in high salinity brines - Hamdi, S.S. (Elsevier Inc., 2020)
The data in this article present the effective parameters of experimental ultrasonication process on the dispersion stability of graphene nanoplatelets (GNPs) grafted with a natural polymer of Gum Arabic (GA). These datasets are supporting the article âNatural Polymer Non-Covalently Grafted Graphene Nanoplatelets for Improved Oil Recovery Process: A Micromodel Evaluationâ 1. The datasets were gained during experiments conducted at various dwell time (30, 60, 90 and 120 min) at constant power amplitude (60%) of sonication for preparing the stable GA-GNP/brine solutions aiming cost-effective and green agent solution for chemical enhanced oil recovery (C-EOR). The GA-GNPs dispersion data was verified using particle size analyser and UVâVis measurements. The optimized time and power amplitude parameters of the sonication process were utilized for preparing stabilized samples of GA grafted GNPs in regarding to research work on Natural Polymer Non-Covalently Grafted Graphene Nanoplatelets for EOR. The dispersion stability of GA-GNPs nanofluids at reservoir conditions of high salinity and high temperatures (HSHT) was further demonstrated in the measured data through the sedimentation of nanoparticles. Â© 2020